Signaling Through gp130 Compromises Suppressive Function in Human FOXP3+ Regulatory T Cells - Bin Dhuban, Khalid; Bartolucci, Sabrina; d'Hennezel, Eva; Piccirillo, Ciriaco A. (Frontiers in Immunology, 2019)
The CD4+FOXP3+ regulatory T cell (Treg) subset is an indispensable mediator of immune tolerance. High and stable expression of the transcription factor FOXP3 is considered a hallmark feature of Treg cells. Using a single-cell cloning strategy that allows the discrimination between activated Teff contaminants and bona fide FOXP3-expressing Treg clones, we have recently shown that the human FOXP3+ Treg population is functionally heterogeneous, containing a sizeable proportion of clones with an impaired capacity to suppress Teff cells despite exhibiting the hallmark surface phenotype of functional Treg cells. We have further demonstrated that this FOXP3-positive, suppression-negative (FPSN) subpopulation, resembles its FOXP3-positive, suppression-positive (FPSP) counterpart in the demethylation status of the Treg-specific demethylated region (TSDR) of the FOXP3 locus, as well as in the global Treg gene expression signature. These findings indicated that these non-suppressive FOXP3+ cells likely originate from previously functional Treg cells. There are currently no markers to delineate these dysfunctional FOXP3+ cells, and their prevalence and potential role in autoimmunity remains unknown. This study aims to characterize the factors that drive loss of suppressive function in human Treg cells, and to identify surface markers of dysfunctional Treg cells. We show that high expression of the IL-6 family cytokine receptor subunit gp130 identifies Treg cells with reduced suppressive capacity ex vivo and in primary FOXP3+ clones. We further show that two gp130-signaling cytokines, IL-6 and IL-27, impair the suppressive capacity of human Treg cells. Finally, we show that gp130 signaling reduces the expression of the transcription factor Helios, whose expression is essential for stable Treg function. These results highlight the role of gp130 in regulating human Treg function, and suggest that modulation of gp130 signaling may serve as a potential avenue for the therapeutic manipulation of human Treg function.